Designing Enggang Bungas Jewelry as a Cultural Expression of the Dayaknese in Kalimantan - Anisa, Anisa; Bahri, Nurul Fitriana (Gorga : Jurnal Seni Rupa, 2024)
The Dayak tribe is a tribe with a very diverse cultural heritage and customs in Kalimantan. The Dayak tribe is known to have a variety of decorative arts with symbols and motifs adapted from the uniqueness of Kalimantan's nature, one of which is the Hornbill (rhinoplax vigil) symbol on its traditional jewelry. Traditional Dayak jewelry is often used in traditional ceremonies and daily activities. However, traditional jewelry derived from Hornbills has begun to be abandoned and replaced by modern-style jewelry. Therefore, it is necessary to introduce the cultural value of the Hornbill symbol to the young generation of the Dayak tribe so that cultural preservation can be expressed and its existence can be maintained. This research aims to design Hornbill motif jewelry that is integrated with contemporary touches and adaptation of traditional elements as a form of cultural expression of the Dayak tribe in Kalimantan. The design method used is the Design Thinking method with a descriptive qualitative approach, the data collection technique used is literature study and observation. The results of this research are in the form of a design of Enggang Bungas jewelry consisting of bracelets, ear cuffs, and necklaces. This research can contribute to the preservation of Dayak culture and become a form of media for cultural expression in Kalimantan.